DEVELOPMENT OF AN ENGLISH PROFICIENCY ASSESSMENT SYSTEM: A WEB-BASED APPROACH - Hilman, Anwar; Yasmin A, Wafiqah; Lestari, Vivi Ayu; Mutawaly, Ahmad Najib; Supriyadi (RISTEC : Research in Information Systems and Technology, 2025)
English proficiency assessment is a vital component of the learning process, especially in tailoring instructional materials to students' needs and abilities. This study aims to develop and implement a web-based English proficiency assessment system that is efficient, adaptive, and capable of providing real-time feedback to users. The research adopts a Design and Development Research (DDR) approach, utilizing the Spiral Model as the software development methodology. The implementation results demonstrate that the system improves the efficiency of assessment processes, reduces manual grading errors, and offers a more interactive learning experience. User evaluations indicate a high level of satisfaction, particularly in terms of accessibility, quick result display, and user-friendly interface design. The study concludes that the developed system not only enables more accurate and relevant language skill assessment, but also contributes to enhancing students’ learning motivation and the overall effectiveness of English language instruction in digital environments.